Application of Response Surface Methodology for Optimizing Arginine Deiminase Production Medium for Enterococcus faecium sp. GR7 - Baljinder Kaur; Rajinder Kaur (The Scientific World Journal)
Arginine metabolism in Enterococcus faecium sp. GR7 was enhanced via arginine deiminase pathway. Process parameters including fermentation media and environmental conditions were optimized using independent experiments and response surface methodology (central composite design). Fermentation media (EAPM) were optimized using independent experiments which resulted in 4-fold increase in arginine deiminase specific activity as compared to basal medium. To further enhance arginine deiminase activity in E. faecium sp. GR7 and biomass production including a five-level central composite design (CCD) was employed to study the interactive effect of three-process variables. Response surface methodology suggested a quadratic model which was further validated experimentally where it showed approximately 15-fold increase in arginine metabolism (in terms of arginine deiminase specific activity) over basal medium. By solving the regression equation and analyzing the response surface cartons, optimal concentrations of the media components (g/L) were determined as arginine 20.0; tryptone 15.0; lactose 10.0; K2HPO4 3.0; NaCl 1.0, MnSO4 0.6 mM; Tween 80 1%; pH 6.0 for achieving specific arginine deiminase activity of 4.6 IU/mG with concomitant biomass production of 12.1 mg/L. The model is significant as the coefficient of determination (R2) was 0.87 to 0.90 for all responses. Enhanced arginine deiminase yield from E. faecium, a GRAS lactic acid bacterial strain, is desirable to explore in vitro therapeutic potential of the arginine metabolizing E. faecium sp. GR7.